(3HSJGf GdCWHGA hQhVI GdCdHGAs - (3ehGab GdOjf CHj fUQ GSYO Hf GdjGS GHf GdeWQGf,J (B587 (3g` s
(3ChdgG (B:s
(3bGd LGeY gPG GdcJGH Efj LGeY dfaSj aj cJGHj gPG JPGcQ eeG CWGdYg hCSeYg ef GdTjhN s
(3BNQgG (B:s
(3eHJhQI GdBNQ, jfJgj GdehLhO efgG Hbhdg(B: (3hEPG bdfG aj GdeQV Efg dG EYJOGd Mbjbj adG jJhge s
(3ef fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B38 ; (3eLdI GdeLeY GdYdei GdYQHi (B- (3GdLRA (B3 - (3U (B2 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B269 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs